Literature Review: Manajemen Perubahan, Tantangan Perubahan dan Model Perubahan - Engkos Kosasih; B. Herawan Hayadi; Furtasan Ali Yusuf; M Haidar Husein; Musadad Musadad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
When it comes to managing change from a human perspective, an approach called change management can be used. Change management has evolved and evolved over the last fifty years. The term